Topographical and Physicochemical Contrast in Photopatterned SU-8 Films for Microfabrication of Multilayer Structures - Salazar Alarcón, Leonardo (2016)
During SU-8 standard photolithography process, a patterned topography is formed with a characteristic height profile produced by the different shrinkage of the UV exposed and masked regions. We study the change of wettability, film solubility, and topographic modifications on SU-8 films of different thicknesses and show its relevance in the formation of spinning-flow arrays on top layers made from positive photoresists. Also, considerable contrast in film solubility and surface energy as observed from contact angle measurements is produced. Interface diffusion of the photoresists was also observed and followed by Rutherford Back Scattering. We discuss the derivations of the mentioned effects concerning the limitations to multilayered microfabrication processes and possibilities to take advantage of the surface profiles obtained.